Irritable Brain Caused by Irritable Bowel? A Nationwide Analysis for Irritable Bowel Syndrome and Risk of Bipolar Disorder - Liu, Chia-Jen (PLoS One, 2015)
OBJECTIVE: We explored the association between IBS and the development of bipolar disorder, and the risk factors for bipolar disorders in patients with IBS. METHODS: We identified patients who were newly diagnosed with IBS between 2000 and 2010 in the Taiwan National Health Insurance Research Database. We also identified a comparison matched cohort without IBS. The occurrence of new-onset bipolar disorder was evaluated in both cohorts. RESULTS: The IBS cohort consisted of 30,796 patients and the comparison cohort consisted of 30,796 matched patients without IBS. The incidence of bipolar disorder (incidence rate ratio, 2.63, 95% confidence interval (CI) 2.10–3.31, P < .001) was higher in the IBS patients than in the matched cohort. Multivariate matched regression models indicated that autoimmune diseases (HR 1.52, 95% CI 1.07–2.17, P = .020), and asthma (HR 1.45, 95% CI 1.08–1.95, P = .013) were independent risk factors for the development of bipolar disorder in the IBS patients. CONCLUSION: IBS may increase the risk of developing subsequent bipolar disorder. Additional prospective studies are required to confirm these findings.